The Age‐Well randomized controlled trial of the Medit‐Ageing European project: Effect of meditation or foreign language training on brain and mental health in older adults. Issue 1 (28th November 2018) - Poisnel, Géraldine; Arenaza‐Urquijo, Eider; Collette, Fabienne; Klimecki, Olga M.; Marchant, Natalie L.; Wirth, Miranka; de La Sayette, Vincent; Rauchs, Géraldine; Salmon, Eric; Vuilleumier, Patrik; Frison, Eric; Maillard, Aline; et al.
Abstract: Introduction: The Age‐Well clinical trial is an ongoing monocentric, randomized, controlled trial aiming to assess an 18‐month preventive meditation‐based intervention directly targeting the attentional and emotional dimensions of aging to promote mental health and well‐being in elderly people. Methods: One hundred thirty‐seven cognitively unimpaired older adults are randomized to either an 18‐month meditation‐based intervention, a structurally matched foreign language training, or a passive control arm. The impact of the intervention and underlying mechanisms are assessed with detailed cognitive, behavioral, biological, neuroimaging and sleep examinations. Results: Recruitment began in late 2016 and ended in May 2018. The interventions are ongoing and will be completed by early 2020. Discussion: This is the first trial addressing the emotional and cognitive dimension of aging with a long‐term nonpharmacological approach and using comprehensive assessments to investigate the mechanisms. Results are expected to foster the development of preventive strategies reducing the negative impact of mental conditions and disorders. Highlights: Meditation or language training could improve mental health and well‐being in aging. Age‐Well is a randomized controlled trial targeting mental health in aging. Age‐Well includes 18‐month meditation and foreign language training in 137 elderly. Age‐Well interventions are expected to positively impact brain structure and function.